2018
DOI: 10.18314/ctoy.v1i1.1206
|View full text |Cite
|
Sign up to set email alerts
|

Transient Macular Damage during Smartphone Usage

Abstract: A woman in her twenties experienced a central scotoma in her left eye while she was gazing at the visual display of a Smartphone. Her Best Corrected Visual Acuity (BCVA) the following day was 20/15 OD and 20/60 OS. A ringshaped yellowish reflex surrounding the central fovea was observed in the left eye on a fundus photograph, and the inner segment Ellipsoid and Interdigitation Zones (EZ and IZ, respectively) were defective at the foveola on Optical Coherence Tomography (OCT). Ten days later, her BCVA became 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Evidence is mounting that chronic exposure of the visible blue light can cause oxidative damage to the ocular tissues. 20,61 Further investigation is necessary to identify the quantity of short-wavelength light required for a physiologically functional balance, without causing damage to ocular tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence is mounting that chronic exposure of the visible blue light can cause oxidative damage to the ocular tissues. 20,61 Further investigation is necessary to identify the quantity of short-wavelength light required for a physiologically functional balance, without causing damage to ocular tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent in vivo studies have examined retinal damage from blue light in rats and mice, 1618 and human clinical experience is being reviewed and reported. 19,20…”
mentioning
confidence: 99%
“…This phenomenon is highlighted as a potential consequence of excessive smartphone usage, shedding light on the impact of digital devices on ocular health, especially in younger populations. 26 Scholars recorded that patients with TSB had similar eye conditions of differential bleaching of retinal photopigment. The observations indicated that the eye not covered by a pillow adjusted to light, while the covered eye adapted to darkness.…”
Section: Pathophysiologymentioning
confidence: 99%